법과학 적용을 위한 한국인 Y-STR 단상형 데이터베이스의 확장 - 조남수; 최동호; 김양정; 홍승범; 김순희; 이원해; 한면수 (과학수사학회지, 10(1), 2016)
Y 염색체 STR을 이용하는 남성 특이적인 DNA프로필 개인식별은 범죄현장 증거물 분석에서 이용되고 있다. 그러므로 남성 상염색체 STR 결과가 없는 증거물에서 분석될 수 있는 혈통관계 마커들의 일치확률 계산은 DNA 수사에서 중요한 사항이다. 혈통관계 마커의 일치 빈도를 측정하기 위한 참고 데이터베이스로서 검증을 위해, 범죄현장 1133개의 증거물 샘플로부터 Y 염색체 STR 단상형(haplotype)을 분석하였다. 이들 단상형은 총 1133개의 DNA 샘플을 이용해서 23개의 Y 염색체 STR 유전자좌위들(DYS576, DYS389I, DYS448, DYS389II, DYS19, DYS391, DYS481, DYS549, DYS533, DYS438, DYS437, DYS570, DYS635, DYS390, DYS439, DYS392, DYS643, DYS393, DYS458, DYS385a/b, DYS456, and Y-GATA H4)을 분석하였다. 그 결과 null 대립유전자, duplicated 대립유전자 및 microvariant 대립유전자와 같은 중요하고 특이적인 대립유전자들이 관찰되었다. 또한 기존 보고된 자료들과 함께 대립유전자 빈도와 단상형 기초 변수들이 계산되었다. 23개의 혈통관계 마커로 구성된 한국인 Y 염색체 STR 데이터베이스는 법과학적 적용에 있어서 일치빈도 측정을 위한 유용한 참고 방법으로 활용되어질 것으로 생각된다. The identification of male-specific DNA profiles using Y chromosomal short tandem repeat (STR) systems is frequently performed in forensic casework. Therefore, the estimation of match probabilities for these lineage marker (No male results of autosomal STR from crime scene) is an important problem in DNA investigation. For validation as the reference database for estimating the frequency of lineage markers, we analyzed the Y chromosomal STR haplotypes from 1133 subject samples in crime scene. These haplotypes were analyzed for 23 short tandem repeat (STR) loci (DYS576, DYS389I, DYS448, DYS389II, DYS19, DYS391, DYS481, DYS549, DYS533, DYS438, DYS437, DYS570, DYS635, DYS390, DYS439, DYS392, DYS643, DYS393, DYS458, DYS385a/b, DYS456, and Y-GATA H4). A considerable atypical allele number of null, duplicated and microvariant alleles were revealed. The Allele frequencies and haplotype-based parameters were calculated and compared with those of previously reported data. It seems that our expanded Korean YSTR haplotypes consisted with these 23 lineage markers are useful reference method for estimation of matching frequencies in forensic practice. KCI Citation Count: 1